Pelatihan Matematika Dasar Menggunakan Media Animasi Jarimatika Bagi Anak-Anak TPQ Masjid Baitul Muhsinin Sumbang - Yuli Purwati; Esa Damayanti; Imung Dwi Upaya (Politeknik Negeri Cilacap, 2021)
The children's activities at the TPQ Baitul Muhsinin Mosque are currently only carried out 3 times a week so that on other days there are no activities for children at the mosque, eventually some of them choose to play gadgets or watch television. To fill in activities other than reciting recitation and filling in activities on empty days, the solution offered in this service activity is to provide basic math training for children at TPQ by using the finger animation media. This training was chosen because numeracy skills have many benefits for children, including enabling children to better understand the universe and the laws that apply in it, enabling children to plan and evaluate well as adults, enabling children to make designs and constructions correctly. , teach children to be fair, train children to shop properly and not easily cheated and many other benefits. The method chosen in the animation media is the Jarimatika method, which is one way to perform arithmetic operations. It is called Jarimatika because it is done by using your fingers to help solve Arithmetic. With this training, it is hoped that the children's activities at the TPQ Baitul Muhsinin Sumbang Mosque will be more active and varied because there are other activities that can be done besides reciting the Koran, they can use animation media at home to learn by involving parental participation, The results of this training activity the children were able to solve addition and subtraction problems using the Jarimatika method quickly and precisely and was fun because they used their fingers to count.